Find the values of the constants $a$,$b$ and $c$ such that the ellipse $4x^2+y^2+ax+by+c=0$ passes through the point $(-1,2)$ and is tangent to the x-axis

What I've done so far:

Substitute $(-1,2)$ in $4x^2+y^2+ax+by+c=0$:

$$\begin{align} &\implies 4+4-a+2b+c=0 \\ &\implies c=a-2b-8 \tag{1} \end{align}$$

Rewriting the equation of the ellipse to get standard form:

$$\begin{align} & 4x^2+y^2+ax+by=-c \\[6pt] \implies& 4\left(x^2+\frac{a}{4}x+\frac{a^2}{64}\right) +\left(y^2+by+\frac{b^2}{4}\right)=a-2b-8+\frac{a^2}{16}+\frac{b^2}{4} \\[6pt] \implies& \frac{4\left(x+\frac{a}{8}\right)^2}{a-2b-8+\frac{a^2}{16}+\frac{b^2}{4}}+\frac{\left(y+\frac{b}{2}\right)^2}{a-2b-8+\frac{a^2}{16}+\frac{b^2}{4}}=1 \end{align}$$

Since the ellipse is tangent to the $x$-axis:

$$\begin{align} &\quad\sqrt{a-2b-8+\frac{a^2}{16}+\frac{b^2}{4}} = \frac{b}{2} \\[6pt] \implies&\quad a-2b-8+\frac{a^2}{16}+\frac{b^2}{4} = \frac{b^2}{4} \\ \implies&\quad 2b= a-\frac{a^2}{16}-8 \tag{2} \end{align}$$

From $(1)$ and $(2)$:

$$\quad c= a-\left(a-\frac{a^2}{16}-8\right)- 8 \quad\implies\quad c= \frac{a^2}{16} \tag{3}$$

Therefore, the equation of the ellipse becomes


That is, $$\frac{\left(x+\frac{a}{8}\right)^2}{b^2/16}+\frac{\left(y+\frac{b}{2}\right)^2}{b^2/4}=1 \tag{4}$$

I'm stuck at this point and don't know how to find $a$ (or what else to do in general).

All help is appreciated.

  • 1
    $\begingroup$ I think the question misses an additional information about the ellipse. For different values of $a$, you'll get different ellipses, each of which would be tangent to the x-axis, and pass through $(-1,2)$. $\endgroup$ – Tejas Sep 22 '17 at 17:35
  • $\begingroup$ So will any value do? I don't think it needs a specific ellipse , just one that has the properties given in the question $\endgroup$ – Dahen Sep 22 '17 at 17:40
  • $\begingroup$ If all that you have to do is come up with a single answer, then, yes, pick a convenient value for $a$ and simplify. Is there any particular reason that you need to give the equation in standard form? Why not just plug the values that you’ve found into the original equation? $\endgroup$ – amd Sep 22 '17 at 21:22
  • $\begingroup$ @amd I guess because I'm kinda familiar with the form? Dunno why myself tbh it was what I used when I first tried this. But well it'll be a lot easier to simplify from the original equation once ive chosen a value for (a) so i'll do that $\endgroup$ – Dahen Sep 22 '17 at 21:25

There's not one, but an infinite number of ellipses that satisfy the two conditions that you have listed. You have 3 unknowns ($a$,$b$ and $c$) to solve for, but only 2 conditions given by which you can determine them. So, no unique solution.

Note that the equation of the ellipse can be written as $$\frac{(x+\frac{a}{8})^2}{(\frac{1}{2})^2} + \frac{(y+\frac{b}{2})^2}{1^2} = \frac{a^2}{4^2}+\frac{b^2}{2^2}+c \equiv D^2$$.

Some edits: I forgot to divide out by $D^2$ to put it in standard form. So, $$\frac{(x+\frac{a}{8})^2}{(\frac{D}{2})^2} + \frac{(y+\frac{b}{2})^2}{D^2} = 1$$. This shows that the half axis along the y-direction has length D. Since the ellipse is tangent to the x-axis, the center of the ellipse $(\frac{-a}{8},\frac{-b}{2}$ must be exactly D above the x-axis. In other words, $\frac{-b}{2}=D$ or $\frac{b^2}{4}=D^2$.
$$\frac{a^2}{4^2}+\frac{b^2}{2^2}+c = \frac{b^2}{4}$$ This is one equation relating $a$,$b$ and $c$. The other is obtained by plugging $(x,y)=(-1,2)$ in to the equation of the ellipse to get the second equation

$$\frac{(x+\frac{a}{8})^2}{(\frac{1}{2})^2} + \frac{(y+\frac{b}{2})^2}{1^2} = D^2 = \frac{b^2}{4}$$.

Any combination of $a$, $b$ and $c$ that satisfy the two equations above, will give a valid ellipse that meets the two conditions you are given.

| cite | improve this answer | |
  • $\begingroup$ Yes I found out that if you let a equal any real number your ellipse will still satisfy the question. thanks for the help $\endgroup$ – Dahen Sep 23 '17 at 8:26

Your equation $(1)$ is correct: $$a - 2 b - c = 8 \tag{1}$$

For the tangency condition, you're thinking a little too hard. If the ellipse is tangent to the $x$-axis, then the equation should have a double-root for $x$ when $y=0$; that is, its discriminant must vanish: $$4 x^2 + a x + c = 0 \quad\to\quad \text{discriminant} = a^2 - 4\cdot 4\cdot c = 0 \quad\to\quad a^2 = 16 c \tag{2}$$

... which is, of course, your $(3)$. Now, two independent equations aren't enough to specify three unknowns. There are lots of solutions here. Since $a^2 \geq 0$, we know $c$ is non-negative; take $c := (2d)^2$ for some $d$ (the factor of $2$ helps us avoid some fractions), and we have

$$a = \pm 8 d \qquad b = -2( d^2 \mp 2 d + 2 ) \qquad c = 4d^2 \tag{3}$$

For completeness, the equation of the ellipse is ... $$4 \left(x \pm d \right)^2 + \left( y -(d^2\mp 2 d+2) \right)^2 = (d^2\mp 2 d + 2)^2 \tag{4}$$

Note that the vertical radius is $\left|d^2\mp 2 d + 2\right|$, which matches the vertical offset of the center, easily re-confirming the tangency property. $\square$

| cite | improve this answer | |
  • $\begingroup$ The way I used the tangency property was probably alot more complicated than it should have been. I never thought of thinking the discriminant , thanks $\endgroup$ – Dahen Sep 23 '17 at 8:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.